Application Of The Profile Matching Method In The Selection Of Field Implementers (CV. AGRAPANA WIDJAYA) - Ramdhany, Tri; Firmansyah, Devie; Aryanggara, Yanwar (Indonesian Operations Research Association (IORA), 2023)
The activity of selecting the right person to carry out a job within a company organization is not only to get superior quality resources, but it is also important for managers to get fluency in the work being done. The problem of selecting candidates for field implementation at CV. Agrapana Widjaya, that is, it is difficult to get candidates who match the candidate criteria desired by the company, the number of candidates to be selected with a limited deadline is often the manager's subjective assessment of each candidate. The solution to this problem is to create a web-based decision support system by applying the profile matching method approach which can later do gap weighting, grouping the main factors, supporting factors, and the final calculation of each candidate. So that this can be done by giving recommendations in the form of ranking results where every candidate who has great value is the candidate who has the greatest chance of getting the job. The results of this study are the project manager at CV. Agrapana Widjaya is expected to make it easier to carry out the assessment process and provide an overview of each candidate for decision-making.